Ytterbium triflate promoted coupling of phenols and propiolic acids: synthesis of coumarins. Issue 26 (29th June 2016) - Fiorito, Serena; Epifano, Francesco; Taddeo, Vito A.; Genovese, Salvatore
Graphical abstract: Highlights: A new method for the synthesis of coumarins is reported. A new application of ytterbium triflate catalysis. First example of a coupling between phenols and alkynoic acids promoted by microwave irradiation. Abstract: Coumarins are a well-known class of natural occurring and semi-synthetic products with reported important and effective pharmacological activities. In this Letter an improved method for the chemical synthesis of such compounds is described. Coumarins have been obtained in good to excellent yields under microwave irradiation and solvent-free conditions in a short time from differently substituted phenols and propiolic acids used as starting materials in the presence of Yb(OTf)3 hydrate 10% mol as the catalyst.